Performance comparison of the thermal behavior of xylitol and erythritol in a double spiral coil latent heat storage system. (1st March 2020) - Anish, R.; Mariappan, V.; Joybari, Mahmood Mastani; Abdulateef, Ammar M.
Highlights: Compared the thermal performance of erythritol and xylitol in an energy storage unit. Erythritol exhibited superior charging characteristics than xylitol. No subcooling effect was noticed during the discharging of xylitol. The result of this analysis is helpful for the design of PCM based solar thermal systems. Abstract: Phase change material (PCM) based thermal energy storage systems decrease fossil fuel consumption and can help to reduce environmental impacts. However, extensive application of PCMs are hindered owing to their low thermal conductivity, causing slow charging and discharging processes. In the present work, a comparison of the thermal performance of two medium temperature sugar alcohol based PCMs of erythritol (C4 H10 O4 ) and xylitol (C5 H12 O5 ) in a vertical double spiral coil unit is presented. Effects of the operating parameters such as volume flow rate and inlet temperature of the heat transfer fluid (HTF) Therminol-55 on the phase change behavior of the PCMs were investigated. Temperature variation of PCMs at different locations of the storage unit, melt fraction and heat storage/discharge rate were obtained. Melting of PCMs was a faster process owing to the impact of natural convection. Furthermore, the double spiral coil storage unit provided suitable thermal performance, achieving high PCM melting rate. Quantitatively, erythritol stored 790 kJ of heat in 60 min for an HTF inlet temperature of 155 °C. For the same flow rate and HTF temperature difference, xylitol stored 450 kJ of heat in 35 min. Therefore, erythritol exhibited superior charging characteristics than xylitol; however, subcooling obstructed the discharging performance of erythritol. On the other hand, no subcooling effect was noticed during the discharging of xylitol.